2013
DOI: 10.2174/15748898113089990001
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Inhibition as a Possible Therapeutical Approach to Protect Cells from Death in Neurodegenerative Diseases

Abstract: Transglutaminases are ubiquitous enzymes which catalyze post-translational modifications of proteins. The main activity of these enzymes is the cross-linking of glutaminyl residues of a protein/peptide substrate to lysyl residues of a protein/peptide co-substrate. In addition to lysyl residues, other second nucleophilic co-substrates may include monoamines or polyamines (to form mono- or bi-substituted /crosslinked adducts) or -OH groups (to form ester linkages). In absence of co-substrates, the nucleophile ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…new avenues for neurodegenerative therapeutic research (43). It is interesting to note that we found that AMI significantly attenuated the expression of transglutaminase 2 in the hippocampus and the striatum.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 61%
See 1 more Smart Citation
“…new avenues for neurodegenerative therapeutic research (43). It is interesting to note that we found that AMI significantly attenuated the expression of transglutaminase 2 in the hippocampus and the striatum.…”
Section: Volume 290 • Number 5 • January 30 2015mentioning
confidence: 61%
“…For example, Tppp (tubulin polymerization-promoting protein) and Acsl5 (acyl-CoA synthetaselong-chainfamilymember5)andSdhc(succinatedehydrogenase complex, subunit C, integral membrane protein, 15 kDa) are strongly implicated in mitochondrial function and metabolic support (81)(82)(83). AMI also consistently up-regulated the expression of factors associated with neuronal development (Sparc, secreted protein, acidic, cysteine-rich (osteonectin)) (84), neuronal Akt-mediated protection (Nyap1, neuronal tyrosine-phosphorylated phosphoinositide-3-kinase adaptor 1), and attenuation of neurodegenerative cross-linking (Tgm2, transglutaminase 2) (43,85). With our use of PAGE MSigDB bioinformatics analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous systemic and topical antibiotic and antiseptic agents have been used for the prevention and treatment of burn wound infections (BWI), with the rationale for application of topical therapy predominantly related to prophylaxis of BWI. It is postulated that topical therapy may reduce the microbial burden in the burn wound, thereby reducing the risk of infection and potentially promoting wound healing (36,37,40,41).…”
Section: Wound Infection Following Burn Injuriesmentioning
confidence: 99%
“…Several clinical trials are being tested for TGase 2 inhibitors. Cysteamine is known to target active site cysteine residues and has been launched as a potential therapeutic for a broad range of disease indications including cystic fibrosis [20], neurodegenerative diseases [21], and Huntington’s disease [22], amongst others by Raptor pharmaceuticals, Mylan, and the European Institute for Cystic Fibrosis Research [19]. Zedira has focused on developing peptidomimetic TGase 2 inhibitors which mimick the TGase 2 substrate for the treatment of celiac disease.…”
Section: Introductionmentioning
confidence: 99%